Properties of snail shell-immobilized lipase of Aspergillus pseudotamarii and its application in butyl butyrate synthesis - Garuba, Emmanuel O; Otemoye, Opeyemi (Journal of BioScience and Biotechnology, 2024)
In this study, attempts were made to evaluate shells of egg and snail, crystal beads, and kaolin clay as suitable carriers for the immobilization of purified lipase produced by Aspergillus pseudotamarii. The free and immobilized lipases were characterized and applied in the synthesis of butyl butyrate. Snail shell yielded 84.17% immobilization efficiency, surpassing other carriers. Optimal activity occurred at 40℃ and 45℃, yielding 2.0U/ml and 3.0U/ml for free and immobilized lipase, respectively. Immobilized lipase demonstrated superior thermal stability (62.6% vs. 0% at 300 min). pH influenced activity, with maxima at pH 7 and 6.5 for immobilized and free lipase. Kinetic parameters: Km, Vmax—3.17mM, 0.549 µM/min (free); 0.214mM, 0.894 µM/min (immobilized). Immobilized lipase exhibited better storage stability. Butyl butyrate synthesis favored immobilized lipase (71.85% vs. 52.38% yield). Optimization studies showed that the immobilized lipase achieved the highest conversion yield at a shorter reaction time and higher temperature compared to the free lipase. The immobilized lipase also exhibited excellent reusability, maintaining a stable conversion yield over multiple cycles. Overall, the immobilized lipase on snail shell showed promising characteristics and potential for butyl butyrate synthesis.